Semiotics in Political Discourse. An Analytical Treatment of Political Text Criticisms Since 2003: The Case of the Discourse of Prime Minister Nouri Al-Maliki - Arif, Jasim Muna; Jawad, Hadi Nahla (International Journal of Criminology and Sociology, 2022)
This article discusses the function of semiotics in political discourse after the socio-political processes taking place in Iraq since 2003 and its role in the development of textual criticisms of some Iraqi politicians, analyzes the reasons for its functioning in the speech of politicians. The research is mainly focused on finding out to what extent political text studies draw on sign systems that can store and transmit information, the nature of its purpose and the use of available fields for the purpose to be achieved. The chief purpose of the study is to investigate and also clarify the symbols and signs appear within the framework of discursive Iraqi politicians, the nature of the symbols used, and the meanings that are included in the discourse in terms of structure, context, and form. Moreover, it has been attempted to define semiotic features in the texts of Iraqi politicians; and elicit structure, style and wording, and the degree of convergence of meaning and form in the semiotic application.